The Fractured Self and the Primacy of the Future Edward Schillebeeckx and the Eschatological Horizon - Minch, Daniel 1986- (2016)
In light of the problem of the postmodern "de-centered" subject for Christianity, I address the loss of a common expectation horizon of the eschatological future. This loss is situated within the wider collapse of modern metanarratives and the dispersal of the primacy and critical power of the future, leading to an incomplete and even shattered process of identity formation for Christians. By recovering elements of Edward Schillebeeckx's eschatology, I suggest a way forward by drawing on the wider Christian tradition and hope for salvation as an essential element for the ongoing process of identity formation, while using his thought to critique the fractured postmodern "self" and contemporary trends in culture, religion, and economics.
Keywords: Edward Schillebeeckx; Jean-François Lyotard; Eschatology; Hermeneutics; master narratives; Postmodernism; Temporality